Investigating indirect influences of team composition on team innovation: qualitative evidence from parallel teams in Malaysian organizations - Abdullah, M.; Quaddus, Mohammed (ANZAM, 2011)
This article reports qualitative findings on how team composition influences team innovation through ‘team interaction processes’ and ‘emergent states’, which can be described by the ‘team reflexivity’ and ‘team innovation climate’ variables. Given that team composition generally related to ‘bio-demographic’ and ‘task-related’ diversities, this study explores which diversity is related to team reflexivity and innovation climate. Data were collected through semi-structured interviews with members of parallel teams in Malaysian organizations. Content analysis of the interview transcripts revealed that bio-demographic diversity affects only one of the four dimensions of the innovation climate, which then influences team reflexivity. Task-related diversity was found to have a direct influence on team reflexivity, but was not related to any dimension of the innovation climate.